Changes in launch delay and availability of pharmaceuticals in 30 European markets over the past two decades - Melanie Büssgen; Tom Stargardt (BMC Health Services Research, 2022)
Abstract Background The timing of the launch of a new drug is an important factor that determines access for patients. We evaluated patient access to pharmaceuticals in 30 European markets over the past two decades. Methods Launch dates were extracted from the IQVIA (formerly IMS) database for 30 European countries for all pharmaceuticals launched internationally between 2000 and 2017. We defined launch delay as the difference between the first international launch date and the corresponding national launch date, and calculated these for each country in our sample over time. Additionally, we ranked countries according to their launch delays and looked at changes in the ranking order over time. Lastly, we determined the availability of new pharmaceuticals in each country, calculating this as the percentage of these pharmaceuticals that were available in each country during a pre-specified interval. Results There was a clear trend towards a decrease in launch delays across all countries from 2000 (37.2 months) to 2017 (11.8 months). Over the entire observation period, the three fastest launching countries were the Netherlands, Sweden, and Germany, whereas the three slowest were Bosnia-Herzegovina, Serbia, and Turkey. Germany had the highest availability of new pharmaceuticals with 85.7%, followed by the United Kingdom (83.1%) and Norway (82.9%). Countries with the lowest availability of pharmaceuticals were Bosnia-Herzegovina, Serbia, and Latvia. Gross domestic product per capita was negatively correlated with launch delay (-0.67, p < 0.000) and positively correlated with the availability of pharmaceuticals (+ 0.19, p < 0.000). Conclusion Launch delay and the availability of pharmaceuticals varied substantially across all 30 European countries. Using countries with above-average availability and below-average launch delays as a benchmark, stakeholders may discuss or modify current pharmaceutical policy, if needed, to improve access to pharmaceutical care.